Elementos para uma teoria sistemática da elisão tributária - Galbinski, Diego (2016)
In contempt of the paradigmatic crisis, the systematic theory of tax avoidance is a particular case of systematic theory of Tax Law. It proposes models of problems and solutions for legal phenomenon of tax avoidance from the inference by analogy of the fundamental right of tax freedom. In addition to a subjective dimension, this unenumerated right has an objective dimension, which unfolds in interpretative and protection duties, and a broad statement of facts, which permits the practice of neutral economic relations to the greatest extent possible. Based on the principle of ability to pay, the Brazilian tax system restricts the fundamental right of tax freedom by specific anti-avoidance rules and general anti-avoidance rule. Mobile anti-avoidance rules arise as a third way to promote the stability and predictability values and to reduce the administrative and judiciary discretions.